2012
DOI: 10.1111/j.1863-2378.2012.01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Multiple Genotypes of Calicivirus Infection in Asymptomatic Swine in Taiwan

Abstract: Noroviruses (NoVs) and sapoviruses (SaVs) of the family Caliciviridae are emerging enteric pathogens in humans and animals. Recent detection of genogroup II norovirus (GII NoV) RNA from swine raises public health concerns about zoonotic transmission of porcine NoVs to humans. However, few papers reported genotype distributions and epidemiological features in swine farms and their genetic relationship to human strains, which was the objective of our study. This study investigated the epidemiological features an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 49 publications
0
41
0
4
Order By: Relevance
“…These differences could be due to different geographical locations, different ages of pigs sampled, or the use of different detection methods and primers with various specificities. Most porcine NoVs belong to the typical porcine genotypes (GII.11, -18, and -19), but human GII NoV-like RNA (GII.2, -3, -4, and -13) was occasionally detected from pigs in Asia (8,15). Overall there was no significant prevalence difference among the disinfection treatments (biocides and water control; see Table S1 in the supplemental material).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…These differences could be due to different geographical locations, different ages of pigs sampled, or the use of different detection methods and primers with various specificities. Most porcine NoVs belong to the typical porcine genotypes (GII.11, -18, and -19), but human GII NoV-like RNA (GII.2, -3, -4, and -13) was occasionally detected from pigs in Asia (8,15). Overall there was no significant prevalence difference among the disinfection treatments (biocides and water control; see Table S1 in the supplemental material).…”
Section: Discussionmentioning
confidence: 84%
“…Even though different ages of pigs were tested, NoVs were detected only in finisher pigs (7). A Canadian study reported 25% prevalence (41), and many other studies found lower prevalence rates: 2% to 4.6% in Europe (5, 42), 9% in New Zealand (43), 8% in Brazil (44), and Ͻ1% to 15% in Asia (8,15,22). These differences could be due to different geographical locations, different ages of pigs sampled, or the use of different detection methods and primers with various specificities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Norovirus is mostly detected in finisher swine, whereas Sapovirus has been found in all different age groups of swine [10,12]. Swine illnesses are associated with porcine Sapovirus while the influence of Norovirus contagions in swine is unknown [3].…”
Section: Introductionmentioning
confidence: 99%